2009
DOI: 10.1099/vir.0.008656-0
|View full text |Cite
|
Sign up to set email alerts
|

Virulence variation among isolates of western equine encephalitis virus in an outbred mouse model

Abstract: Little is known about viral determinants of virulence associated with western equine encephalitis virus (WEEV). Here, we have analysed six North American WEEV isolates in an outbred CD1 mouse model. Full genome sequence analyses showed ¡2.7 % divergence among the six WEEV isolates. However, the percentage mortality and mean time to death (MTD) varied significantly when mice received subcutaneous injections of 10 3 p.f.u. of each virus. Two WEEV strains, McMillan (McM) and Imperial 181 (IMP), were the most dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
51
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(59 citation statements)
references
References 34 publications
6
51
2
Order By: Relevance
“…We have previously shown that i.n. exposure of outbred CD-1 mice to WEEV.McM leads to virus entry into the CNS through the long axonal projections of olfactory sensory neurons (OSNs) (6,7) and supports other studies showing that VEEV and EEEV utilize OSNs as an important route of entry into the brain following i.n. or aerosol inoculation (8)(9)(10).…”
supporting
confidence: 62%
See 1 more Smart Citation
“…We have previously shown that i.n. exposure of outbred CD-1 mice to WEEV.McM leads to virus entry into the CNS through the long axonal projections of olfactory sensory neurons (OSNs) (6,7) and supports other studies showing that VEEV and EEEV utilize OSNs as an important route of entry into the brain following i.n. or aerosol inoculation (8)(9)(10).…”
supporting
confidence: 62%
“…A full-length infectious clone of the WEEV.McM was derived from a virus isolate obtained from the Arbovirus Reference Collection at the Centers for Disease Control and Prevention in Fort Collins, CO, and has been previously described (6). Passage history for virus strains used has been previously published (13,14).…”
Section: Virusesmentioning
confidence: 99%
“…Cell culture supernatants were collected at 48 h postinfection (hpi) and stored in aliquots at Ϫ80°C. Virus titers were determined by plaque assay on Vero cells as previously described (26).…”
Section: Methodsmentioning
confidence: 99%
“…McM when administered IN also causes extensive damage to the neurons of the CNS. The alterations in pathogenicity between the two strains are possible attributed to either slower replication of the attenuated strain or changes in the response to the innate immune system (Logue, et al, 2009). Accumulated data from EEE and VEE indicate that alterations in response of the host and susceptibility of the virus to the immune response are a strong determinant of outcome.…”
Section: Mouse Modelmentioning
confidence: 99%
“…Like in humans, age and strain of mouse infected, route of inoculations, and virulence of virus strain all influence the susceptibility of the host (Aguilar, 1970;Bianchi, et al, 1993;Logue, et al, 2009;Monath, et al, 1978;Nagata, et al, 2006). Peripheral routes of infection result in approximately 50% mortality with intracerebral (IC) or intranasal (IN) challenge resulting in more uniform, dose-dependent mortality depending on strain of virus and background of murine model (Hardy, et al, 1997;Julander, et al, 2007;Liu, et al, 1970).…”
Section: Mouse Modelmentioning
confidence: 99%